Caffeic Acid-Containing Medium for Identification of Cryptococcus neoformans - Hopfer, Roy L. (J Clin Microbiol, 1975)
A new growth medium containing caffeic acid and ferric citrate is described. The pigment produced on this medium is specific for the identification of Cryptococcus neoformans and differentiates it from other cryptococci. The medium is more easily compounded and requires less time for pigment formation than the conventional Guizotia extract media. The medium is stable in the dry form as well as in the prepared form. IMAGES: